MUSICAL REPRESENTATION OF THE RELIGIOUS MESSAGE IN ZOLTÁN GÁRDONYI’S "HÁROM NAGYHETI KÉP (THREE HOLY WEEK EVENTS)" - Gabriela COCA (Studia Universitatis Babeş-Bolyai. Musica, 2021)
Zoltán Gárdonyi (1906-1986) composed his work entitled Három Nagyheti Kép (Three Holy Week Events) in 1966. At that time, he was a professor at the Liszt Ferenc Academy of Music, in Budapest. He composed the work for organ and a string ensemble (1st violin, 2nd violin, viola, cello, double bass). The work has three movements, as the title Három Nagyheti Kép (Three Holy Week Events) suggests.[1] This paper analyses the work in question in detail, from a harmonic and formal point of view.